Woman See Lots of Things - Asher, Mira (Body Lab Art Foundation ; Lela Films, 2006)
Verzio FF Submission “Woman See Lots of Things” is an experimental documentary about three female ex-child combatants who were participants in the Liberian and Sierra Leonean civil wars of the 1990s‭.‬ During these decade-long civil wars‭, ‬numerous girls were abducted‭, ‬raped and forcibly recruited‭. ‬Others volunteered in order to find protection‭. ‬They were used as fighters‭, ‬sex-slaves and laborers by all parties in the conflicts‭. ‬In addition to combat duties‭, ‬many were subject to constant sexual abuse‭; ‬some taken as‭ ‬‮‘‬wives‮’‬‭ ‬by rebel commanders‭, ‬impregnated and forced to brutalize others‭.‬ Anita Jackson, Mahade Pako and Chris Conteh came from different social backgrounds. They had different roles in the wars, and found themselves after the wars in contrasting situations, and holding different views. Anita was born in Liberia and she was a volunteer fighter and a nurse in SLA (Sierra Leone Army) and AFRC junta (Armed Forces Revolutionary Council) during the war. Chris was born in Sierra Leone. She was abducted and fought with the RUF junta (Revolutionary United Front). Mahade was born in Liberia, and she too was abducted. She fought with ULIMO (United Liberian Movement for Democracy). This film tries to understand their lives in post-war Sierra Leone, and the psychophysical adjustments they have undertaken in order to come to terms with their experiences.